The Influence of Financial Performance on Stock Prices in Banking Companies Listed on the Indonesia Stock Exchange (IDX) - Nur Arini Susanti; Ilham A. Fattah; Akbar M (www.amertainstitute.com, 2024)
The population in this study is the banking sector that went public on the Indonesia Stock Exchange, totaling 31 banks. The sample was determined using a purposive sampling technique with the aim of obtaining a representative sample according to the specified criteria. The sample in this study was 5 banking companies. There are two variables in this study, namely: Independent variables include CAR, RORA, NPM, ROA, and LDR. While the dependent variable is the change in stock prices in banking companies on the IDX and uses the multiple regression method. Based on the research results, it is known that there is a significant influence between CAR, RORA, NPM, and ROA on the stock price of banking companies on the Indonesia Stock Exchange partially, meaning H1 is accepted. While for LDR partially, it is known that it does not have a significant influence on stock prices in banking companies on the Indonesia Stock Exchange, meaning Ho is accepted. For simultaneous testing, there is a significant influence between variables X1, X2, X3, X4, and X5 together on Y (Stock Price) in public banking companies, H1 is accepted.